Analisis Kelayakan Pemberian Kredit UKM pada BPR Artha Panggung Perkasa di Trenggalek - Novi Puji Lestari; Muhammad Jihadi; Achmad Fahruddin (Universitas Muhammadiyah Sidoarjo, 2018)
Banking is a financial institution that exists in Indonesia which has an important role for the sustainability of the Indonesian economy. Economic growth must be directed at increasing people's incomes and overcoming economic inequality with social inequality. Economic growth in order to increase people's income, needs to be given attention to efforts to foster and protect small and traditional businesses and weak economic groups. Credit distribution is an important part of helping the economy and this is one of the tasks of the BPR. The Case Study conducted at BPR Panggung Perkasa Trenggalek, moreover their focus is on Small and Medium Enterprises. Credit distribution needs to be developed by providing loans to productive sectors, namely Small and Medium Enterprises.